Representasi Feminisme di Iklan Minuaman Olatte Versi “Taste Of Friendship Ep 1 (Cara Ranty Ungkapin Hati)” - Annisa Widya Paramitha; Turnomo Rahardjo (Kalijaga Journal of Communication, 2022)
ABSTRACT The rapid development of advertising in recent years, since there are many factors, such as: development of modernisation, culture and also internet. Nowadays, advertisement not only find in the television, but you also easily find the advertisement in social media. Youtube is the most used social media, since they have number 1 rank in Indonesia as the favourite of social media, the percentage of the score is 93,8%. This research used semiotics theory by John Fiske to analysis the data. The result of this research finds 3 level from the Olatte’s advertisement, such as: Level of reality, in this level find the4 codes (dress, speech, gesture, makeup and expressions). The second one is level of representation, in this level the researcher find 3 codes (Teknik of camera, lighting and music). The last one in the level of ideology, the researcher finds the liberal of feminism used in this advertisement, also liberal feminism is the most dominant that used in this advertisemet.